The Effect of Immune responses In Pathogenesis of Hepatitis B Virus Patients - alwan, J abbar afat; Njum, Ali Anok (International Journal of Psychosocial Rehabilitation, 2020)
Study attempts to estimate immune molecules CD45- R & CD79 and cytokines TNF-α and IL-6 in patients infected with HBVA total of (100) seropositive patients for HBV were screened for this study .Patients attended general lab, because of abdominal pain , jaundice and loss of appetite and other liver complaint, any serum samples expressed positive for anti-HBV antibodies directly choose to show level of TNF-α & IL-6 in serum of patient and show expression of CD45-R and CD79. Results showed that serum samples were analyzed for IL-6 & TNF-α by ELISA , showed highly significant increases (p